2023
DOI: 10.1007/s10549-023-06944-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between gout and subsequent breast cancer: a retrospective cohort study including 67,598 primary care patients in Germany

Abstract: Purpose The aim of this retrospective cohort study was to analyze the cumulative incidence of breast cancer following gout and to investigate the association between gout and subsequent breast cancer in 67,598 primary care patients in Germany. Methods This study included adult female patients (≥ 18 years) with an initial diagnosis of gout in 1284 general practices in Germany between January 2005 and December 2020. Individuals without gout were matched to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…It has previously been shown that the panel of practices included in the Disease Analyzer database is representative of private practices in Germany [ 17 ]. Finally, this database has already been used in previous studies focusing on breast cancer [ 18 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has previously been shown that the panel of practices included in the Disease Analyzer database is representative of private practices in Germany [ 17 ]. Finally, this database has already been used in previous studies focusing on breast cancer [ 18 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…This enzyme converts hypoxanthine to uric acid and generates reactive oxygen species. A high level of uric acid in the blood leads to the development of gout, which increases the risk of breast cancer. , Although several anticancer drugs are available, the number of cancer patients still increases, partly due to the ability of cancer to develop resistance through various mechanisms, such as drug inactivation, drug efflux, and inhibition of cell death . In addition, anticancer drugs are expensive, limiting their accessibility to patients and their potential for adverse side effects.…”
Section: Introductionmentioning
confidence: 99%